Формування інформаційного забезпечення розвитку вантажних перевезень АТ “Укрзалізниця” - Двуліт, З. П.; Селюченко, Н. Є.; Dvulit, Z. P.; Seliuchenko, N. Y. (Видавництво Львівської політехніки, 2021)
Розвинено методичний підхід до формування показників інформаційної бази розвитку вантажних перевезень АТ “Укрзалізниця” та її філій, що полягає у розрахунку показників таксономії із обґрунтуванням статичних та динамічних систем. Здійснено просторове і часове порівняння вантажних перевезень виокремлених систем за 2002– 2019 рр. Запропонований методичний підхід може бути використаний не тільки в управлінні вантажними перевезеннями, але й у прийнятті рішень щодо економічного розвитку АТ “Укрзалізниця” та її філій, а також інших великих компаній.

A methodical approach to the formation of indicators of the information base of management decisions on the development of freight JSC “Ukrzaliznytsia”, which consists in calculating the taxonomy of the level of development of freight by substantiating systems and its elements: eighteen static systems, elements of which are six regional railways; seven dynamic systems – regional branches and in general JSC “Ukrzaliznytsia”. A spatial and temporal comparison of the development of freight transportation of selected systems is carried out. The taxonomy index is calculated on the basis of five indicators of freight traffic for the period 2002–2019. The analysis of static systems made it possible to identify the uneven development of freight transportation of regional branches of JSC “Ukrzaliznytsia” for the studied 18 years. The temporal comparison of the levels of development of freight traffic by each railway in particular also showed their instability. Fluctuations are observed in the last three years of the study period. In 2018, JSC “Ukrzaliznytsia” demonstrated the lowest level of freight transportation development for the entire analyzed year 2002–2019. It was established that both external and internal factors caused the negative impact on rail transportation, in particular: the economic crisis of 2014–2015; military action in eastern Ukraine; ineffective management at different levels of government. The introduction of quarantine measures due to the Covid-19 pandemic caused unprofitable and deteriorating financial and economic performance of JSC Ukrzaliznytsia, and its six regional branches in 2020, in particular, revenues from freight transportation decreased by 10.3 % compared to 2019, and net loss amounted to UAH 11.9 billion. Implementing the anti-crisis plan by the management of JSC Ukrzaliznytsia and the improvement of operational work in the freight segment has yielded some positive results. However, for the effective planning and management decisions in the field of freight transportation an important component is the proper formation of an information base. The proposed methodological approach will serve as an effective tool not only in the management of the freight segment of individual regional branches or enterprises in particular, but also the economic development of JSC “Ukrzaliznytsia” in general and can be used by other large companies.
Formation of information support for the development of freight transportation of JSC “Ukrzaliznytsya”
Keywords: рейтингування; регіональні філії; АТ “Укрзалізниця”; вантажні перевезення; інформаційне забезпечення; управлінські рішення; метод таксономії; система; rating; regional branches; JSC “Ukrzaliznytsia”; freight transportation; information support; management decisions; taxonomy metho; 004.942; 656.073